Pengaruh Persepsi Keadilan Organisasi Terhadap Perilaku Suara Karyawan Melalui Pertukaran Pemimpin-Anggota Pada PT Cahaya Bumi Musi - Ketut Aldo; Ignatius Soni Kurniawan; Tri Ratna Purnamarini (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2026)
Background – In a dynamic organizational environment, employee participation through voice behavior plays an essential role in enhancing organizational effectiveness and innovation. One of the factors believed to influence voice behavior is Perceived Organizational Justice (POJ), which encourages employees to express their ideas and opinions constructively. In addition, the quality of the relationship between leaders and members (Leader–Member Exchange / LMX) also has the potential to strengthen this influence. Therefore, it is important to understand how organizational justice perceptions affect employee voice behavior, both directly and through leader–member relationships. Aim – This study aims to examine the effect of Perceived Organizational Justice (POJ) on Employee Voice Behavior (EVB) with Leader–Member Exchange (LMX) as a mediating variable among employees of PT Cahaya Bumi Musi. Design / methodology / approach – This study employs a quantitative approach with a survey method. This study employed a quantitative survey design using a census approach involving all 50 employees of PT Cahaya Bumi Musi. Data were collected through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. Findings – The results show that POJ has a positive and significant effect on EVB, as well as a positive and significant effect on LMX. However, LMX does not have a significant effect on EVB and does not mediate the relationship between POJ and EVB. Conclusion - Perceived organizational justice has a positive and significant effect on employee voice behavior and leader–member exchange at PT Cahaya Bumi Musi. However, leader–member exchange does not have a significant effect and does not mediate the relationship between organizational justice and employee voice behavior, indicating that organizational justice plays a more dominant role. Research implication – The findings provide practical implications for management to develop a transparent and participative organizational justice system to encourage employees to express ideas and constructive suggestions. Limitations – This study is limited to one company, namely PT Cahaya Bumi Musi, so the generalization of the results should be made with caution. Future research is recommended to include different industrial sectors and consider contextual factors such as organizational culture and leadership style.